2009
DOI: 10.4012/dmj.28.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photocuring strategy on bonding of dual-cure one-step self-etch adhesive to root canal dentin

Abstract: This study evaluated the effects of light power density and light exposure time on regional bond strength of Clearfil DC Bond to root canal dentin. Post spaces were prepared in extracted premolars. Root canal dentin was treated with a dualcure bonding system, Clearfil DC Bond, and light-cured for 10, 20, or 30 seconds using two halogen light curing units: Optilux 501 (830 mW/cm 2 ) and Hyperlightel (1350 mW/cm 2 ). Following which, all post spaces were filled with a dual-cure resin composite. After 24-hour sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
16
0
2
Order By: Relevance
“…This characteristic might be a result of incomplete solvent removal within the adhesive layer. 34 In a fibre post-bonded canal, besides failure at the dentine-resin interface, some specimens failed cohesively within the post structure. In the authors' previous study, it was demonstrated that the bond strengths of a Snowlight-bonded canal were 22.8 and 19.9 at the coronal and apical regions, respectively, and that all specimens cohesively failed within the post.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic might be a result of incomplete solvent removal within the adhesive layer. 34 In a fibre post-bonded canal, besides failure at the dentine-resin interface, some specimens failed cohesively within the post structure. In the authors' previous study, it was demonstrated that the bond strengths of a Snowlight-bonded canal were 22.8 and 19.9 at the coronal and apical regions, respectively, and that all specimens cohesively failed within the post.…”
Section: Discussionmentioning
confidence: 99%
“…Direct layering of SFRC into the root canal is intended to solve these drawbacks. Seyam et al and other authors showed that a transparent post can transfer the light and aid the polymerization of composite resin in the root canal, [56][57][58] enabling layering in the hollow root canal space. However, there are investigations to oppose this statement [59,60].…”
Section: Groupmentioning
confidence: 99%
“…15 The use of prolonged curing time was reported to aid in the effective curing of the apical part and thus in obtaining homogenous bonding throughout the canal length. 16 Also, the additional use of the light-transmitting posts in successive sizes to apply resin material in layers to control the Cfactor while achieving effective curing presents an attractive solution to bonding to weakened root canals. Previous work highlighted the success of this approach to achieve proper bonding to different root levels.…”
Section: Introductionmentioning
confidence: 99%